Correlational study on idiopathic neonatal hyperbilirubinemia and closure time of ductus venosus - Lu Cai; Zhengying Li; Zhijun Zhang; Wei Wang; Yiyi Cao; Tao Xie; Hui Wang (Annals of Medicine)
Objective To investigate the correlation between idiopathic neonatal hyperbilirubinemia and ductus venosus closure time and to examine prenatal factors influencing DV closure in neonates.Methods A total of 103 full-term hyperbilirubinemic neonates born between September 2022 and September 2023 were selected as the hyperbilirubinemia group, while 169 full-term healthy neonates were chosen as the control group. Neonates with other perinatal or maternal abnormalities were excluded. Ultrasonographic examinations monitored ductus venosus closure time. ductus venosus blood flow, umbilical vein blood flow, ductus venosus shunt fraction, middle cerebral artery pulsitility index, and estimated fetal weight at term were retrospectively analyzed to compare differences between the two groups. The correlation between neonatal serum total bilirubin and ductus venosus closure time, as well as prenatal influences on ductus venosus closure time in neonates, were evaluated.Results The hyperbilirubinemia group had significantly longer ductus venosus closure time than the control group (p < 0.05). A positive association was found between ductus venosus closure and elevated neonatal serum total bilirubin. Prenatal factors influencing ductus venosus closure time included ductus venosus shunt fraction and fetal weight, where lower fetal weight and higher ductus venosus shunt fraction were associated with a delayed ductus venosus closure in neonates.Conclusion Ductus venosus closure time is positively correlated with idiopathic neonatal hyperbilirubinemia, suggesting a potential role in its development. Fetal weight and the ductus venosus shunt fraction during the fetal period appear to influence the timing of ductus venosus closure in neonates.